Nativized Hispanic Borrowed Words In Waray Visayan News Articles: A Lexical Analysis (Journal of Namibian Studies : History Politics Culture, 2023)
This research study examines the nativization process of Hispanic borrowed words in Waray Visayan news articles, focusing on lexical categories, English equivalents, root words, Spanish equivalents, native affixes, and orthographic nativization. Nine articles from Bombo Radyo Tacloban were analyzed, providing textual data for the investigation. The study employs the theories of phylogenetic change through linguistic borrowing and borrowing transfer theory to reveal significant findings.The results indicate that the Waray Visayan news articles feature 68 nouns, 12 verbs, and 10 adjectives borrowed from Spanish. All 67 borrowed nouns demonstrate linguistic acculturation through lexical nativization. The 12 verbs from Spanish exhibit nativized spelling and the addition of native affixes. Additionally, the ten borrowed adjectives undergo orthographic changes and acquire native Waray Visayan affixes.The analysis suggests that the Hispanic borrowed words in Waray Visayan undergo acculturation by nativizing their orthography, which aligns with the language's phonetic nature. Furthermore, the addition of affixes represents a clear process of lexical nativization. Consequently, the study concludes that Hispanic words borrowed in Waray Visayan are acculturated through lexical nativization.This research highlights the need for further exploratory studies on nativized Hispanic borrowed words in Waray Visayan across various genres of mass media, literary texts, and verbal communication. These studies have the potential to enhance language learning, benefiting language teachers, lexicographers, and related disciplines. By expanding our understanding of the acculturation process in linguistic borrowing, this research contributes to the broader field of language studies.